Selection of Thrust Restraints for Above Ground Pressure Pipes With Expansion Joints - S., Paulraj (AMC Indian Journal of Civil Engineering, 2018)
Pressure pipes used in various industrial applications are subjected to internal pressures of a high order by the fluids carried by them. Though such pipes of various materials of construction are designed to withstand these pressures, strength and stability of pipes at bends either below or above ground require careful examination to achieve external equilibrium specifically when diameters are large. The following discussion is intended to bring forth the different industrial practices in addressing the question of external stability of pipes at bends above ground under various operating conditions. It presents an analysis on the right selection of thrust restraints for such applications.